Model Peramalan Pasang Surut Menggunakan Pendekatan Artificial Neural Network (ANN) - Muhammad Arrafi Irsyad; Andy Hendri; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Previous researchers have much success using the model Artificial Neural Network (ANN) as a forecasting model for hydrological analysis. Reliability of ANN models need to be tested, especially to farecast of the tidal. In this research, Adaptive Neuro Fuzzy Inference System (ANFIS) models which built using data tidal observations in Tanjung Buton (2004). The result of tidal forecasting by using ANN models show excellent results with value the test statistic parameters of the correlation coefficient (R) more than 0.8774 that is in category of very strong correlation, statistic parameters of Root Mean Square Error (RMSE) 0.4362 m, and the test parameters of the average valuation relative error by 11.57%. Keywords: Tidal, Artificial Neural Network, Backpropagation, Tanjung Buton